Surgical treatment of postinfarction left ventricular aneurysm in 32 patients. Issue 12 (December 1976) - Donaldson, R M; Honey, M; Balcon, R; Banium, S O; Sturridge, M F; Wright, J E
Abstract : Thirty-two patients with large postinfarction left ventricular aneurysms shown at operation to consist of fibrous tissue are reported. All had angina and/or breathlessness, and none had a history of embolism. Thirty were correctly diagnosed by left ventricular cineangiography. Two of the 3 patients with inferior and 1 with an anterior aneurysm had associated ventricular septal defects, and 3 patients with an anterior aneurysm had mitral regurgitation. All had major coronary arterial lesions and 68 per cent had double or triple vessel disease. The aneurysm was excised in all patients; in 15 this was combined with saphenous vein bypass grafting of coronary arteries supplying surviving myocardium, in 3 with closure of a ventricular septal defect, and in 3 with mitral annuloplasty or replacement. Operative mortality was 6-2 per cent, and 79 per cent of the survivors are asymptomatic with average follow-up period of 18 months after operation.